2015
DOI: 10.4178/epih/e2015009
|View full text |Cite
|
Sign up to set email alerts
|

Oral symptoms significantly higher among long-term khat (Catha edulis) users in Ethiopia

Abstract: OBJECTIVES:Associations between khat (Catha edulis) chewing and different adverse oral-dental health conditions have been reported, yet evidence is still lacking. This study was designed to investigate the association between long-term regular khat chewing and self-reported oral symptoms.METHODS:A cross-sectional study was conducted on a sample of 1,255 university students in southern Ethiopia. Data on khat chewing status, a range of oral symptoms and other pertinent variables were collected using self-adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…The association between khat chewing and xerostomia has been well documented in the literature . Al‐Alimi et al.…”
Section: Oral Manifestations Of Khat Usagementioning
confidence: 90%
See 1 more Smart Citation
“…The association between khat chewing and xerostomia has been well documented in the literature . Al‐Alimi et al.…”
Section: Oral Manifestations Of Khat Usagementioning
confidence: 90%
“…Astatkie et al. reported that 16.6% of khat chewers complained of mouth dryness . Interestingly, the development of severe xerostomia is well documented in abusers of amphetamine and its derivatives, such as methamphetamine, which are chemically similar to cathinone, the active component of khat…”
Section: Oral Manifestations Of Khat Usagementioning
confidence: 99%
“…The growing research evidence shows that khat is a risk factor for different cardio-vascular disorders such as hypertension, ischemic heart diseases, and stroke 3,4 . Khat is also a risk factor for poor oral health 5 , psychosis 6 , mental distress 7 , anemia 8 , poor quality of life 9 , disturbed sleep pattern [10][11][12] , and duodenal ulcer 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The leaves of khat or the powder of Shammah are usually kept in the buccal vestibule of the mouth, or occasionally the lingual or lower labial vestibules for Shammah. 27,28 Both habits have been put forward as risk factors for a negative effect on oral health, which might end with teeth mortality. Also, khat chewers had significantly more tooth loss than non-khat-chewers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, khat chewers had significantly more tooth loss than non-khat-chewers. [28][29][30] Others have proposed consumption of Khat and Shammah as major reasons for tooth wear. 40 As noted in previous studies Al Moaleem 26 and Bayaty et al, 27 many of the oral health problems of Yemen subjects have been associated with Khat and there is a widespread belief that periodontal disease is more severe in khat chewers than non-chewers, ultimately leading to tooth mortality (Table 4).…”
Section: Discussionmentioning
confidence: 99%